The complete mitogenome of Argas vulgaris (Filippova, 1961) and its phylogenetic status in subgenus Argas (Acari: Argasidae) - Yi-Fei Wang; Jia-Jing Zheng; Ming-Zhu Zhang; Li-Feng Du; Xiao-Ming Cui; Xiao-Yu Han; Di Tian; Nuo Cheng; Ning Wang; Wan-Ying Gao; Bai-Hui Wang; Xiao-Yu Shi; et al. (International Journal for Parasitology: Parasites and Wildlife, 2024)
Soft ticks (Ixodida: Argasidae) are ectoparasites of terrestrial vertebrates with worldwide distributions. As one representative group of Argasidae, the genus Argas has an important vectorial role in transmitting zoonotic diseases. However, our knowledge of the subgenus Argas in China is still limited, as most literature only lists occurrence records or describes specific case reports without providing detailed morphological characteristics and further molecular data. This study aims to characterize Argas vulgaris through complete mitochondrial sequencing and morphological diagnostic techniques based on a batch of adult specimens collected from Ningxia Hui Autonomous Regions (NXHAR), North China. The morphology and microstructures of Ar. vulgaris and other lectotypes of argasid ticks in the subgenus Argas were also observed using a stereomicroscope. Following DNA extraction and sequencing, a complete mitochondrial sequence of Ar. vulgaris was assembled and analyzed within a phylogenetic context. The 14,479 bp mitogenome of Ar. vulgaris consists of 37 genes, including 13 genes for protein coding, two for ribosomal RNA, 22 for transfer RNA, and one for control region (D-loops). Phylogenetic analysis of Ar. vulgaris showed 98.27%–100% nucleotide identity with Ar. japonicus, indicating a close relationship between the two tick species. The morphological diagnostic features to differentiate Ar. vulgaris from other ticks within the subgenus Argas included the location of the anus and setae on the anterior lip of the female genital aperture. This study provided high-resolution scanning electron microscope images of female Ar. vulgaris and corresponding molecular data, representing valuable resources for future accurate species identification.